Agrilac: Integración mitigación del cambio climático y desarrollo sostenible - Casallas Martinez, Ivon Maritza; Yomayuza Herrera, Karoll Valentina; Pradel, Willy; Vanegas Cubillos, Martha Cristina (2024)
The AgriLAC Resilient project drives strategies that integrate climate change mitigation with sustainable development objectives in agroecosystems and value chains across Latin America and the Caribbean. This video highlights key achievements, including the implementation of Sustainable Land Use Systems (SLUS), the creation of enabling conditions for sustainable practices, the strengthening of value chains, and the mobilization of resources through innovative mechanisms. With a participatory approach, these actions contribute to territorial resilience and agro-food sustainability.